Mustard, Potherb—Brassica juncea (L.) Czern. var. japonica (Thunb.) Bailey - James M. Stephens (EDIS)
This document provides an overview of potherb mustard (Brassica juncea var. japonica), an oriental leafy green also known as mizuna or Japanese greens. It describes the plant’s appearance, cultivation practices suitable for Florida’s cool season, and its culinary uses. The plant is noted for its attractive, deeply notched leaves and mild flavor. It can be consumed raw or cooked and is rich in vitamins and minerals. Original publication date May 1994.